2020
DOI: 10.1002/art.41469
|View full text |Cite
|
Sign up to set email alerts
|

Antirheumatic Disease Therapies for the Treatment of COVID‐19: A Systematic Review and Meta‐Analysis

Abstract: Objective Antirheumatic disease therapies have been used to treat coronavirus disease 2019 (COVID‐19) and its complications. We conducted a systematic review and meta‐analysis to describe the current evidence. Methods A search of published and preprint databases in all languages was performed. Included studies described one or more relevant clinical outcomes in five or more people who were infected with SARS‐CoV‐2 and were treated with antirheumatic disease therapy betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 80 publications
(77 reference statements)
0
52
0
3
Order By: Relevance
“…By June 2020, the data from large, well-designed observational studies and emerging evidence from RCTs pointed towards a lack of efficacy for antimalarials in the treatment of COVID-19. The systematic review and meta-analysis by Putman, et al reported data from 45 studies up until May 2020, which included hospitalized COVID-19 patients who were treated with medications commonly used as antirheumatic therapies medication [ 25 ]. When pooled, the three included cohort studies assessing HCQ did not demonstrate an association with COVID-19 mortality.…”
Section: Efficacy Of Antimalarials For Covid-19mentioning
confidence: 99%
“…By June 2020, the data from large, well-designed observational studies and emerging evidence from RCTs pointed towards a lack of efficacy for antimalarials in the treatment of COVID-19. The systematic review and meta-analysis by Putman, et al reported data from 45 studies up until May 2020, which included hospitalized COVID-19 patients who were treated with medications commonly used as antirheumatic therapies medication [ 25 ]. When pooled, the three included cohort studies assessing HCQ did not demonstrate an association with COVID-19 mortality.…”
Section: Efficacy Of Antimalarials For Covid-19mentioning
confidence: 99%
“…It should be noted that 24% of patients treated with high doses of anakinra developed adverse effects that required discontinuation of the drug, including bacteremia and elevations in liver enzymes [ 7 ]. In a meta-analysis of both studies, anakinra was associated with a significantly lower risk of mortality (pooled HR: 0.2; CI 0.1–0.4) [ 66 ]. Table 2 summarizes the ongoing actively recruiting, phase 3 or 4 clinical trials using anakinra.…”
Section: Interleukin-1 Inhibitorsmentioning
confidence: 99%
“…Eine COVID-19-Erkrankung unter einer fortgesetzten immunsuppressiven DMARD("disease modifiying antirheumatic drug")-Therapie oder eine COVID-19-Erkrankung in einer Situation, in der wir durch eine Therapiepause möglicherweise einen Schub der Grunderkrankung provozieren, was uns zu einer mittelhoch oder hoch dosierten Glukokortikoidtherapie zwingen würde? In beeindruckender Geschwindigkeit haben zur Klärung die-ser Frage nationale und internationale wissenschaftliche Allianzen Register für rheumatologische Patienten mit SARS-CoV-2-Infektion ins Leben gerufen, und die ersten Publikationen daraus liegen bereits vor [4][5][6][7]. Während die verschiedenen Register den Fokus klar auf die infizierten Patienten richten, lag unser Interesse neben der Inzidenz und dem Verlauf der Infektion in unserer Kohorte auch darauf, wie mit nicht an COVID-19 erkrankten Patienten hinsichtlich der Fortführung ihrer Therapie verfahren wird.…”
Section: Verlaufsbeobachtung Einer Universitären Rheumaambulanzkohortunclassified
“…Eine Therapiereduktion oder -beendigung erfolgte nur bei Patienten mit einem stabilen Krankheitsverlauf. Zudem wurde die fachspezifische Literatur aufmerksam nach Daten bei Rheumapatienten verfolgt und unsere Therapiestrategie entsprechend angepasst [4][5][6]. Results.…”
Section: Therapiestrategieunclassified
See 1 more Smart Citation